(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This work describes an experience teaching of Experimental Behavior Analysis concepts, using personalized instruction, known as the Keller System, with adaptations to the semester deadlines imposed by the public university in Brazil. The text begins with a description of central features of the original Keller System, followed by an overview of its application in courses at various universities across the country. In addition, we describe our adapted methodology compared to the original model, pointing out advances and difficulties in our attempt to apply this system based on recent experiences and in light of nearly 30 years of application of that system to teach Behavior Analysis principles.